New Approach to Interpret the Firm Evolution - Abatari, Seyed Amir Yazdanparast; Rezaifar, Omid; Kheyroddin, Ali (Journal of History Culture and Art Research, 2017)
Abstract This article is a preliminary step to introduce a new approach for interpreting how a firm evolves. The core idea of this approach is to verify the firms as the dynamic organization which can change and gain different trait upon time. The change and adaption mechanism can be explained through evolutionary theory. This approach could be used as a good tool to interpret reaction of firms to future environmental and internal changes. To achieve this goal, the firm has been defined as a set of Resource, Ideas and capabilities (RIC). As evolutionary theory has been adopted, a wining rule needs to be determined for selection and struggle process. This winning rule has been developed using the transaction cost theory to verify the effect of this so called RIC mechanism, over 200 hours’ interview has been set up to identify and trace a changing capability in Iranian Construction industry. Applying this view to gathered information shows the power of this method for analyzing the firm’s capabilities.